Strategic leadership of portfolio and project management - Kloppenborg, Timothy J. 1953- (Supply and operations management collection, 2012)
1. Implementing strategy through portfolios and projects -- 2. Managing a portfolio to implement strategy: a leadership team role -- 3. Sponsoring successful projects -- 4. Leading project managers: the project executive role -- 5. Listening to customers, employees, and processes: a chief projects officer's role -- 6. Understanding information technology opportunities and challenges: a chief information officer's role -- 7. Making sensible decisions using data: a responsibility of all executives -- 8. Conclusions -- Notes -- References -- Index